Effectiveness of health teaching on knowledge regarding home care management among women following total Abdominal Hysterectomy admitted in selected hospital, Bangalore. - Yadav, Ragini Kumari (2014)
ABSTRACT: The present study is aimed to assess the effectiveness of health teaching regarding home care management among women following Total Abdominal Hysterectomy in selected hospital, Bangalore. Objectives of the study are 1. To assess the level of knowledge of the women regarding home care management following Total Abdominal Hysterectomy. 2. To assess the effectiveness of health teaching regarding home care management among women following Total Abdominal Hysterectomy. 3. To find the association between the knowledge of women with selected demographic variables. A Pre experimental one group pre test post test design is adopted for this study. The tools used for this study are structured knowledge questionnaire. The reliability of tools is established (0.78). Pilot study is conducted. The data are collected from 30 women following total abdominal hysterectomy using non probability purposive sampling techniques. The data is analyzed and interpreted using descriptive and inferential statistics. The findings reveals that the overall mean pretest knowledge score is 12.7 and the overall posttest knowledge score is 17.83 respectively. The mean posttest knowledge score of women who are exposed to health teaching are significantly higher, than the mean pretest knowledge scores. 't' [29] = 12.48**[P<0.05] and it is assessed at 0.05 level of significance. Hence the research hypothesis [H1] is accepted. There is no significant association between the sociodemographic variables such as age, religion, education qualification, occupation, family monthly income, place of residence, type of family, previous hospitalization, previous surgery and number of child birth following total abdominal hysterectomy so the alternative hypothesis [H2] is rejected. The study concludes that, the health teaching is an effective teaching strategy to enhance the knowledge of women, regarding home care management following total abdominal hysterectomy. Therefore, educating the women regarding home care management following total abdominal hysterectomy through health teaching and word of mouth can be an effective tool for generating awareness and for modification of their lifestyles. KEY WORDS: effectiveness, health teaching, home care management, total abdominal hysterectomy.